HIV Neuroinflammation: The Role of Exosomes in Cell Signaling, Prognostic and Diagnostic Biomarkers and Drug Delivery - Mahajan, Supriya D.; Ordain, Nigel Smith; Kutscher, Hilliard; Karki, Shanta; Reynolds, Jessica L. (Frontiers in Cell and Developmental Biology, 2021)
HIV-1 associated neurocognitive disorders (HAND) remain frequent and occur in nearly 50 to 60% of HIV-1 patients despite the increased availability of antiretroviral therapy (ART) regimens. These disorders, include but are not limited to, confusion, behavioral changes, headaches, cognitive motor impairment and anxiety disorders, are a burden on the health care system. Persistent inflammation, oxidative stress, metabolic disturbances, blood-brain barrier (BBB) dysfunction, and ART drug neurotoxicity in the central nervous system (CNS) are likely contributing factors to the progression and severity of HAND. While much is known about the role microglia and astrocytes play in HAND pathogenesis, the role of exosomes in HIV neuroinflammation and neuropathogenesis is a rapidly developing field. Exosomes are phospholipid bilayer membrane vesicles 50–150 nm in size. They are responsible for a plethora of biological functions under normal and pathological conditions, including cell-to-cell communication, signal transduction, transport of genetic materials, and modulation of immune responses. Due to their diverse intracellular content, exosomes, are poised to provide insight into HIV neuroinflammation as well as provide for diagnostic and predictive information that will greatly enhance the development of new therapeutic interventions for neuroinflammation. Exosomes are also uniquely positioned to be vehicles to delivery therapeutics across the BBB to modulate HIV neuroinflammation. This mini-review will discuss what is known about exosome signaling in the context of HIV in the brain, their potential for biomarkers as well as their potential for vehicles to delivery various therapeutics to treat HIV neuroinflammation.